On density of fourier coefficients of a function of Wiener's class - Siddiqi, Rafat; Al-Alami, Reem (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper we study the problem of density of positive and negative Fourier sine and cosine coefficients of a funtion of Weiner's class Vp whieh is a strietly larger class than the class of functions of bounded variation. In this connection we also extend a classical theorem of Fejér on the determination of the jump of a function of bounded variation to Wiener's class.